The Influence of the Merdeka Curriculum on the Digitalization of Religious Education Learning - Ghozali, Imam; Zamzami, Moh Rifqi; Imawan, Moh Riswandha; Illiyyina, Izzah; Zuhri, Syaifuddin (LPPM Universitas Ibn Khaldun, Bogor, 2025)
The development of digital technology has driven significant transformations in Islamic Religious Education learning, particularly since the implementation of the Independent Curriculum. This study aims to analyze the influence of the Independent Curriculum on the digitalization of Islamic religious education learning, and how it shapes student behavior patterns, understanding of religious values, and engagement in the learning process. This study uses a qualitative approach with a literature review as the primary method, which examines various relevant literature on technology integration in religious learning. The results show that the Independent Curriculum encourages learning flexibility, strengthens digital competencies, and improves students' religious literacy through interactive media. However, challenges were also identified, such as the risk of exposure to negative content and the digital access gap. With the strategic role of teachers as facilitators and guides, digitalization in the Independent Curriculum has the potential to improve the quality of religious education relevant to the needs of the times.